ANALISIS MISKONSEPSI PESERTA DIDIK MENGGUNAKAN TES DIAGNOSTIK FOUR-TIER PADA MATA PELAJARAN MATEMATIKA MATERI ALJABAR KELAS VII - Alya Farhana Maulida; Iskandar Zulkarnain; Taufiq Hidayanto (FKIP Universitas Mataram, 2023)
Misconceptions are cognitive structures that exist in students but are different from the proper concepts. The purpose of this study was to describe the categories of misconceptions about algebra seen from the four-tier diagnostic test and find out the causes of misconceptions. The research instrument was a four-tier diagnostic test that consisted of four levels, namely multiple-choice questions, the confidence level of answers, reasons, and the confidence level of reasons. This research was conducted using a descriptive qualitative method which aims to study a problem in-depth and describe the misconceptions that occur in algebra. The research subjects were 21 students of class VII A at SMPN 2 Pelaihari. The research results obtained were that there were misconceptions in the sub-matter showing algebraic elements of 38,10%, determining algebraic forms of 42.85%, and performing operations on algebraic forms of 71,40%. This can be seen from the pattern of answers BJ-YJ-SA-YA (Correct Answer-Sure Answer-Incorrect Reason-Sure Reason) and SJ-YJ-SA-YA (Incorrect Answer-Sure Answer-Incorrect Reason-Sure Reason). The cause of misconceptions about algebraic material is that the learning methods used by teachers are less popular with students because they are considered boring and students' low interest in learning algebra.